(3GdUMjaI GdSLGOjIs - (3GdbQTj GdgGTej, CHh GdMSf, Rjf GdYGHOjf, Ydj Hf GdMSjf Hf Ydj Hf CHj WGdH, (B94(3g`s
(3ChdgG (B:s
(3CejQ GdeDefjf Ydj Hf CHj WGdH aj TgQ QHjY GdChd ef SfI SJI YTQ hNeS eFI bQGAI Ydjg hCfG CSeY(B... (3Yf CHjg eJhcd Hf gGQhf bGd dbjJ jMji Hf RjO Hf Ydj HYO bJd CHjg hgh eJhLg Edi NQGSGf aSdeJ Ydjg(B...s
(3BNQgG (B:s
(3aEfj dc eSde CYde Cf GdMLI dc hCfc Chdi HGdaVds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B:4(3, U(B277s
(3GdPQjYI(B: (3L(B13(3, U(B342s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs